A Hepatocyte Nuclear Factor BtabHNF4 Mediates Desiccation Tolerance and Fecundity in Whitefly (Bemisia tabaci). Issue 1 (3rd December 2022) - Wang, Kui; Yang, Zhifang; Li, Xiang; Liu, Shunxiao; Wang, Liuhao; Zhang, Hongwei; Yu, Hao
Abstract: Hepatocyte nuclear factor 4 (HNF4) is essential for glucose homeostasis and lipid metabolism in insects. However, little is known about the role of HNF4 in whiteflies. In the present study, we identified a hepatocyte nuclear factor protein from Bemsia tabaci (Diptera: Drosophilidae) and named it BtabHNF4 . The full-length of BtabHNF4 was 3, 006 bp, encoding a sequence of 434 amino acids that contains a conserved zinc-finger DNA-binding domain (DBD) and a well-conserved ligand-binding domain (LBD). The temporal and spatial expression showed that BtabHNF4 was highly expressed in the female adult stage and abdominal tissues of B. tabaci . A leaf-mediated RNA interference method was used to explore the function of BtabHNF4 in whiteflies. Our results showed that the knockdown of BtabHNF4 influences the desiccation tolerance, egg production, and egg hatching rate of whiteflies. Additionally, BtabHNF4 silencing significantly inhibited the expression level of vitellogenin . These results expand the function of HNF4 and pave the way for understanding the molecular mechanisms of HNF4 in regulating multiple physiological processes.